Intersection of Jurisdictional Competence between Administrative Court, District Court, and Tax Court in Adjudicating Unlawful Acts by Government Bodies and/or Officials - Permana, Tri Cahya Indra; Amiludin, Amiludin (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
The jurisdiction to adjudicate disputes involving unlawful acts by Government Bodies and/or Officials encompasses three institutions, namely the Administrative Court, District Court, and Tax Court. The Administrative Court has authority to adjudicate all disputes involving unlawful acts by Government Bodies and/or Officials, except those specifically designated under the jurisdiction of the District Court and Tax Court. The District Court is empowered to adjudicate citizen lawsuits and breach of contracts committed by Government Bodies and/or Officials. Meanwhile, the Tax Court has jurisdiction to adjudicate factual actions in the field of taxation, customs, and/or excise by the Directorate General of Taxes or the Directorate General of Customs and Excise as stipulated in Article 31 of Law Number 14 of 2002 concerning Tax Court